Surviving my Lymphoma - The disease of sorrow - Ayala Yeheskel1; Aya Biderman2 (Archive of Gerontology and Geriatrics Research - Peertechz Publications, 2019)
personal toolbox. I sat with Dr. F and I cried for the whole hour. I had the feeling that he also wanted to cry, but instead, he listened and contained himself. The psychotherapy continued for 4 years, until I felt that I had "cleaned" the memories of the bad times of my life: I am proud to say that I was born in Jerusalem in September, 1940. My parents were very poor. They came from Poland as young Zionists, just before World War II, and left their families behind. They lived on a Kibbutz, and then moved to Jerusalem where my mother had an aunt.